2015
DOI: 10.3109/08958378.2015.1076545
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cigarette smoking mechanism by real time video-endoscopic documentation

Abstract: Smoking follows a consistent sequence of events, defined by specific anatomic configuration and relatively persistent duration. The fast turbulent flow of the smoke over the narrow glottic aperture and at the areas of bifurcation at the trachea and bronchi may have a role in the high relative risk for carcinoma in these areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Respiration topography may also be used to study the effects of product characteristics on usage behavior due to variations in flow path restriction. Research has identified two main smoking patterns: mouth-to-lung (MTL) [ 13 ] and direct-to-lung (DTL) [ 14 , 15 ]. MTL is typically associated with cigarette use.…”
Section: Introductionmentioning
confidence: 99%
“…Respiration topography may also be used to study the effects of product characteristics on usage behavior due to variations in flow path restriction. Research has identified two main smoking patterns: mouth-to-lung (MTL) [ 13 ] and direct-to-lung (DTL) [ 14 , 15 ]. MTL is typically associated with cigarette use.…”
Section: Introductionmentioning
confidence: 99%